Polymer photovoltaic material containing benzodioxepine unit and preparation and application thereof

CN116925327BActive Publication Date: 2026-10-09SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310732306.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2026-10-09
Estimated Expiration
2043-06-20

AI Technical Summary

Benefits of technology

[0032] (1) The benzodioxanone-containing unit of the present invention has strong electron-withdrawing ability and control space, and can easily prepare polymer donor materials with different highest occupied orbital energy levels. By controlling the difference between the highest occupied orbital energy level of the donor and the lowest unoccupied orbital energy level of the acceptor, a larger open circuit voltage can be obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116925327B_ABST
    Figure CN116925327B_ABST
Patent Text Reader

Abstract

The application belongs to the field of organic optoelectronics, and discloses a preparation method and application of a polymer photovoltaic material containing a benzodioxypyrazine unit. The chemical structural formula of the polymer photovoltaic material containing the benzodioxypyrazine unit satisfies the general formula shown below, wherein the D unit is an electron-donating unit, Ar1 and the pi bridge are conjugated fused ring units, A1 and A2 are electron-withdrawing units, and the polymerization degree n is 5-300. The benzodioxypyrazine unit has strong electron-withdrawing ability and space for regulation, can simply prepare polymer donor materials with different highest occupied orbital energy levels, regulate the difference between the highest occupied orbital energy level of the donor and the lowest unoccupied orbital energy level of the acceptor, obtain a larger open-circuit voltage, and has a higher carrier transport capacity. Therefore, the benzodioxypyrazine unit can be better applied to the active layer of a polymer solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic optoelectronics, and specifically relates to a class of polymer photovoltaic materials containing benzodioxanone units, their preparation methods and applications. Background Technology

[0002] In recent years, with the continuous increase in global energy demand and the growing prominence of energy shortages, photovoltaic devices have come into focus. Compared with inorganic solar cells, polymer organic solar cells possess unique characteristics in energy levels and absorption ranges, offering significant advantages in manufacturing customized photovoltaic cells. They also boast high stability and solution-processability. This has attracted widespread attention, making them one of the most promising materials for various optoelectronic devices over the past decade.

[0003] Over the past decade, significant progress has been made in the research of donor-acceptor (DA) alternating conjugated polymers and small organic molecules. Alternating DA design, a combination of electron-rich donor units and electron-deficient acceptors, has become one of the most useful and powerful strategies for synthesizing narrow-bandgap conjugated materials. Before the donor and acceptor parts are combined, they possess their own highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels. After covalent bonding is formed between the two different parts, the HOMO of the donor segment interacts with the HOMO of the acceptor segment, generating two new occupied molecular orbitals, and the same applies to the LUMO. Only by rationally controlling the polymer donor energy levels and improving the matching degree between donor and acceptor energy levels can higher performance of polymer photovoltaic devices be obtained. Summary of the Invention

[0004] To overcome the shortcomings and deficiencies of the prior art, the primary objective of this invention is to provide a class of polymer photovoltaic materials containing benzodioxane units. Benzodioxane units possess suitable electron-withdrawing capabilities and abundant space for modifying electron-withdrawing intensity. The fused-ring structure endows the series of polymers with good thermal stability, while also enabling the achievement of better phase separation scale and energy level difference, thereby increasing short-circuit current density and open-circuit voltage, and improving photovoltaic performance.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned polymer photovoltaic material containing benzodioxane units.

[0006] Another object of the present invention is to provide the application of the above-mentioned polymer photovoltaic materials containing benzodioxane units in the field of organic photovoltaics.

[0007] The objective of this invention is achieved through the following solution:

[0008] A class of polymer photovoltaic materials containing benzodioxane units have chemical structural formulas that satisfy the general formula shown in Formula I:

[0009]

[0010] In Equation I, D unit is a common electron-donating unit in photovoltaic active layer, Ar1 and π bridge are common conjugated fused ring units, A1 and A2 are common electron-withdrawing units, and the degree of polymerization n is 5-300;

[0011] Furthermore, the D unit described above is preferably at least one of the following chemical structures:

[0012]

[0013] In Equation I, the π-bridge unit is preferably a coupling structure of one or at least two of the following structures:

[0014]

[0015] In Equation I, the Ar1 element is one of the following structures:

[0016]

[0017] In Formula I, elements A1 and A2, as well as elements A1 and A2 in Ar1, are each preferably selected independently from one of the following structures:

[0018]

[0019] In the above structure, R1, R2, R3, R4, and R5 are relatively independent H groups, which are halogens, substituted or unsubstituted groups, and one of the following: alkyl groups having 1-20 carbon atoms, aryl groups having 4-20 carbon atoms, heteroaryl groups having 4-20 carbon atoms, aralkyl groups having 4-20 carbon atoms, heteroarylalkyl groups having 4-20 carbon atoms, aryloxy groups having 4-20 carbon atoms, heteroaryloxy groups having 4-20 carbon atoms, arylalkoxy groups having 4-20 carbon atoms, and heteroarylalkoxy groups having 4-20 carbon atoms. Substitution refers to a group formed when one or more hydrogen atoms are substituted by at least one of halogens, branched alkyl groups, oxygen atoms, alkenyl groups, alkynyl groups, aryl groups, etc.

[0020] The preferred chemical structure of the above-mentioned polymer photovoltaic materials containing benzodioxane units is one of the following structures:

[0021]

[0022] The degree of polymerization, n, ranges from 5 to 300.

[0023] A method for preparing the above-mentioned polymer photovoltaic material containing benzodioxane units specifically includes the following steps:

[0024] Polymers are generated by Stille coupling reaction of dihalogen monomers containing benzodioxanone units (preferably dibromo monomers containing benzodioxanone units) and diorganotin monomers of common photovoltaic D units, under the catalysis of tetra(triphenylphosphine)palladium or palladium acetate / tritert-butylphosphine, at a polymerization temperature of 100-150℃.

[0025] The specific reaction route is shown below, where X is either bromine or iodine:

[0026]

[0027] Preferably, in the preparation method described above, the dibromo monomer containing a benzodioxane unit is prepared as follows: Under inert gas protection and an alkaline environment, a dioxane-hexacyclic ring structure is formed between the aromatic fused ring and the pyrazine via the Williamson reaction. Then, the corresponding dibromo monomer product is obtained via NBS or liquid bromine. A π-bridge unit is then added via Stille or Suzuki coupling reaction. Finally, the final dibromo monomer containing a benzodioxane unit is obtained via NBS or liquid bromine for polymer synthesis. The specific reaction route is shown below:

[0028]

[0029] In the method for preparing the dibromo monomer containing a benzodioxane unit, the alkaline environment is provided by one of cesium carbonate, potassium carbonate, sodium methoxide, and sodium tert-butoxide.

[0030] The above-mentioned polymer photovoltaic material containing benzodioxane units is used in the active layer of polymer solar cells. Its characteristic is that the benzodioxane units simultaneously enhance the conjugation degree along the main chain direction of the polymer molecule and the electron-withdrawing strength of the A units in the DA-type repeating segments, achieving good energy level matching with the acceptor material. A bulk heterojunction thin film is then prepared using a solution processing method to obtain the binary / ternary polymer solar cell active layer. The polymer material containing benzodioxane units serves as the polymer donor material.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0032] (1) The benzodioxanone-containing unit of the present invention has strong electron-withdrawing ability and control space, and can easily prepare polymer donor materials with different highest occupied orbital energy levels. By controlling the difference between the highest occupied orbital energy level of the donor and the lowest unoccupied orbital energy level of the acceptor, a larger open circuit voltage can be obtained.

[0033] (2) The benzodioxanone unit of the present invention utilizes the different induction and conjugation effects of heteroatoms to form an aromatic fused ring as the A unit in the donor DA structure, thereby obtaining a polymer donor material with high carrier transport capability.

[0034] (3) The benzodioxane-containing polymer photovoltaic active layer material of the present invention has good solubility and is suitable for simple and low-cost solution processing. At the same time, the polymer fused ring unit has good stability, which can improve the aging performance and environmental stability of polymer photovoltaic devices. Attached Figure Description

[0035] Figure 1 These are the normalized absorption spectra of polymers P1 to P3.

[0036] Figure 2 These are the current density-voltage curves for preparing all-polymer photovoltaic devices by mixing polymers P1 to P3 with PFA polymer acceptors.

[0037] Figure 3 The open-circuit voltage aging degradation test curves are shown for organic solar cells with P1, P2, and P3 as donors and PFA as acceptor. Detailed Implementation

[0038] The present invention will be further described in detail below with reference to embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto. Unless otherwise specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.

[0039] Unless otherwise specified, all reagents used in the examples are commercially available.

[0040] Example 1

[0041] (1) Synthesis of compound 3

[0042] Under nitrogen protection, compound 1 (1.0 g, 6.17 mmol) and compound 2 (1.34 g, 6.17 mmol) were dissolved in 50 mL of methanol in a three-necked flask, and sodium methoxide (1.67 g, 30.84 mmol) was dissolved in 10 mL of methanol. The mixture was added dropwise to the three-necked flask, and the mixture was heated under reflux for 20 hours. The resulting mixture was precipitated in 300 mL of deionized water, filtered, repeatedly washed with water until neutral, dried under vacuum, and then dissolved in a mixed solvent of 50 mL xylene and 15 mL diethyl ether. The mixture was refluxed for 12 hours to give a bright yellow solid product (1.5 g, 79% yield). 1 H NMR (500MHz, Methanol-d4) δ7.90 (s, 2H).

[0043] (2) Synthesis of compound 4

[0044] Under nitrogen protection, compound 3 (1.0 g, 3.27 mmol) was dissolved in 60 mL of acetic acid, and 1-octylamine (633.2 mg, 4.90 mmol) was slowly added. The mixture was refluxed for 20 h, and then 10 mL of diethyl ether was added. The mixture was reacted at 110 °C for 11 h. The mixture was precipitated in water and extracted three times with diethyl ether and water. The organic phase was dried with anhydrous sodium sulfate and purified by column chromatography to give a pale yellow solid product (0.95 g, 70% yield). 1 H NMR (500MHz, Acetone-d6) δ7.57(s,2H),3.89(d,2H),1.68(m,2H),1.37–1.29(m,4H),1.29–0.85(m,9H).

[0045] (3) Synthesis of compound 5

[0046] Under nitrogen protection, compound 4 (0.5 g, 1.2 mmol) was dissolved in 20 mL of chloroform, heated and stirred at 50 °C, and liquid bromine (chloroform solution, cumulative content 1.15 g, 7.19 mmol) was added dropwise in 6 portions. The reaction was monitored by thin-layer chromatography until compound 4 was completely reacted, for a total of 10 h. The mixture was washed three times with 100 mL of water and dried to obtain an orange-yellow crude product solid (600 mg), which was directly used in the next reaction.

[0047] (4) Synthesis of compound 6

[0048] Under nitrogen protection, compound 5 (600 mg crude product) and trimethyltinthiophene (772.8 mg, 3.13 mmol) were dissolved in 20 mL toluene, and 24.1 mg tetrakis(triphenylphosphine)palladium was added. The mixture was heated and stirred at 100 °C for 9 h. The mixture was precipitated in methanol, filtered, washed, and dried. It was then purified by column chromatography to give 450 mg of an orange-yellow solid. 1 H NMR (500MHz, Chloroform-d) δ7.47(d,2H),7.38(d,2H),7.20(d,2H),3.79(t,2H),1.67–0.86(m,15H).

[0049] (5) Synthesis of monomer M1 used for polymerization

[0050] Under nitrogen protection, compound 6 (500 mg, 0.859 mmol) was dissolved in 20 mL of chloroform, heated and stirred at 50 °C, and liquid bromine (chloroform solution, cumulative content 1.1 g, 6.88 mmol) was added dropwise in four portions. The reaction was monitored by thin-layer chromatography until compound 6 was completely reacted, for a total of 8 h. The mixture was washed three times with 100 mL of water, dried, and purified by column chromatography to give a deep yellow solid (550 mg, yield 87%). 1 H NMR (500MHz, Chloroform-d) δ7.27(d,2H),7.16(d,2H),3.79(t,2H),1.68–0.85(m,15H).

[0051]

[0052] Example 2

[0053] (1) Synthesis of compound 9

[0054] Under nitrogen protection, compound 7 (1.0 g, 5.65 mmol) and compound 8 (1.02 g, 5.65 mmol) were dissolved in 50 mL of methanol in a three-necked flask, and sodium methoxide (1.53 g, 28.24 mmol) was dissolved in 30 mL of methanol. The solutions were added dropwise to the three-necked flask, and the mixture was heated to reflux for 20 hours. The resulting mixture was precipitated in 300 mL of deionized water, filtered, repeatedly washed with water until neutral, dried under vacuum, and then dissolved in a mixture of 50 mL xylene and 15 mL diethyl ether. The mixture was refluxed for 12 hours to give a bright yellow solid product (1.4 g, 87% yield). 1 H NMR (500MHz, Acetone-d6) δ7.89 (s, 2H), 2.41 (s, 6H).

[0055] (2) Synthesis of compound 10

[0056] Under nitrogen protection, compound 9 (1.0 g, 3.52 mmol) was dissolved in 60 mL of acetic acid, and 1-octylamine (682.2 mg, 5.28 mmol) was slowly added. The mixture was refluxed for 20 h, and then 10 mL of diethyl ether was added. The mixture was reacted at 110 °C for 11 h. The mixture was precipitated in water and extracted three times with diethyl ether and water. The organic phase was dried with anhydrous sodium sulfate and purified by column chromatography to give a pale yellow solid product (1.15 g, yield 83%).

[0057] (3) Synthesis of compound 11

[0058] Under nitrogen protection, compound 10 (0.5 g, 1.26 mmol) was dissolved in 20 mL of chloroform, heated and stirred at 50 °C, and liquid bromine (chloroform solution, cumulative content 1.21 g, 7.59 mmol) was added dropwise in four portions. The reaction was monitored by thin-layer chromatography until compound 10 was completely reacted, for a total of 8 h. The mixture was washed three times with 100 mL of water and dried to obtain an orange-yellow crude product solid (540 mg), which was used directly in the next reaction.

[0059] (4) Synthesis of compound 13

[0060] 3-Fluorothiophene (3.0 g, 29.4 mmol) was dissolved in dry tetrahydrofuran (110 mL), cooled to -75 °C, and n-BuLi (2.5 M, 12.9 mL, 32.3 mmol) was added dropwise. The pale green mixture was stirred at -50 °C for 2 hours, then cooled to -80 °C, and triisopropylchlorosilane (6.5 g, 33.7 mmol) was slowly added, with stirring at 30 °C for 12 hours. The resulting mixture was poured into water and extracted with dichloromethane. The extract was concentrated and dried to give 7 g of a pale yellow oil. Yield: 93%. 1 H NMR (500MHz, CDCl3, ppm): 7.43 (q, 1H), 6.88 (q, 1H), 1.39 (m, 3H), 1.10 (d, 18H)

[0061] (5) Synthesis of compound 14

[0062] Compound 13 (10.5 g, 40.6 mmol) was completely dissolved in 150 mL of dry tetrahydrofuran. The mixture was then cooled to -70 °C, and n-BuLi (2.5 M, 24.4 mL, 61.0 mmol) was added dropwise. The dark green mixture was stirred at room temperature for 2.5 h, then cooled again to -70 °C. Trimethyltin chloride (1.0 M, 65.0 mL, 65.0 mmol) was added, and the mixture was stirred at 30 °C for 12 h. The resulting mixture was poured into water and extracted with dichloromethane. The organic phase was concentrated and dried to give 15.3 g of a dark red oil in 85% yield. 1 H NMR (500MHz, CDCl3, ppm): 6.93 (d, 1H), 1.38 (m, 3H), 1.11 (d, 18H), 0.37 (s, 9H)

[0063] (4) Synthesis of compound 15

[0064] Under nitrogen protection, compound 11 (540 mg crude product) and compound 14 (1.23 g, 2.93 mmol) were dissolved in 30 mL of tetrahydrofuran. 45.1 mg of tetra(triphenylphosphine)palladium was added, and the mixture was heated and stirred at 100 °C for 9 h. After returning to room temperature, tetrabutylammonium fluoride (1.28 g, 4.88 mmol) was added, and the mixture was stirred at 30 °C for 1 h. The mixture was precipitated in water, extracted with ethyl acetate, filtered, washed, and dried. The solution was purified by column chromatography to give 400 mg of a yellow solid. 1 H NMR(500MHz,Chloroform-d)δ7.34(d,2H),6.53(d,2H),3.79(t,2H),2.41(s,6H)1.68(p,2H),1.35–1.18(m,10H),0.92–0.86(m,3H).

[0065] (5) Synthesis of monomer M2 used for polymerization

[0066] Under nitrogen protection, compound 15 (500 mg, 0.839 mmol) was dissolved in 20 mL of chloroform, heated and stirred at 50 °C, and liquid bromine (chloroform solution, cumulative content 0.67 g, 4.2 mmol) was added dropwise in three portions. The reaction was monitored by thin-layer chromatography until compound 15 was completely reacted, for a total of 5 h. The mixture was washed three times with 100 mL of water, dried, and purified by column chromatography to give a yellow solid (530 mg, yield 84%). 1 H NMR(500MHz,Chloroform-d)δ7.20(d,2H),3.79(t,2H),2.41(s,6H),1.68(m,2H),1.35–1.18(m,10H),0.92–0.86(m,3H).

[0067]

[0068] Example 3

[0069] (1) Synthesis of compound 19

[0070] Under nitrogen protection, compound 17 (2.0 g, 12.34 mmol) and compound 18 (2.3 g, 12.34 mmol) were dissolved in 70 mL of methanol, and sodium methoxide (3.33 g, 61.69 mmol) was dissolved in 10 mL of methanol. The mixture was added dropwise to a three-necked flask, and the mixture was heated under reflux for 20 hours. The resulting mixture was precipitated in 300 mL of deionized water, filtered, dried, and then dissolved in 40 mL of diethyl ether and 40 mL of xylene. The mixture was stirred for 12 hours. The precipitate was again placed in deionized water, filtered, dried, and then recrystallized from methanol and DMF to purify the product. After vacuum drying, a pale yellow solid particle (3.0 g, yield 88%) was obtained. 1 H NMR(500MHz,DMSO-d6)δ13.35(s,1H),7.66-7.45(d,2H).

[0071] (2) Synthesis of compound 20

[0072] Under nitrogen protection, compound 19 (5.0 g, 18.04 mmol) and sodium hydroxide (3.6 g, 90.19 mmol) were placed in a three-necked flask containing 150 mL of N,N-dimethylformamide. The mixture was heated and stirred at 150 °C for 1 h. While maintaining the temperature, bromoisooctane (4.18 g, 21.64 mmol, mixed in 20 mL of N,N-dimethylformamide) was slowly added, and the reaction was continued for 12 h. The product was precipitated in water, filtered, washed three times with water, and dried to give pale yellow solid particles (6.0 g, yield 85%). 1 H NMR (500MHz, DMSO-d6) δ7.45(s,2H),3.93(m,2H),1.88(t,1H),1.47–1.24(m,8H),0.94–0.84(m,6H).

[0073] (3) Synthesis of compound 21

[0074] Under nitrogen protection, compound 20 (0.5 g, 1.28 mmol) was dissolved in 20 mL of chloroform, heated and stirred at 50 °C, and liquid bromine (chloroform solution, cumulative content 1.64 g, 10.27 mmol) was added dropwise in eight portions. The reaction was monitored by thin-layer chromatography until compound 20 was completely reacted, for a total of 10 h. The mixture was washed three times with 100 mL of water and dried to obtain a yellow crude product solid (600 mg), which was used directly in the next reaction.

[0075] (4) Synthesis of compound 22

[0076] Under nitrogen protection, compound 21 (600 mg crude product) and 2-trimethylstan-3-fluorothiophene (697.2 mg, 2.63 mmol) were dissolved in 20 mL of toluene, and 25.34 mg of tetrakis(triphenylphosphine)palladium was added. The mixture was heated and stirred at 100 °C for 9 h. The mixture was precipitated in methanol, filtered, washed, and dried. It was purified by column chromatography to give 400 mg of a yellow solid. 1 H NMR(500MHz,Chloroform-d)δ7.29(d,2H),6.98(d,2H),3.84(d,2H),1.99(m,1H),1.46–1.33(m,4H),1.33–1.26(m,4H),0.89(m,6H).

[0077] (5) Synthesis of monomer M3 used for polymerization

[0078] Under nitrogen protection, compound 22 (506 mg, 0.859 mmol) was dissolved in 20 mL of chloroform, heated and stirred at 50 °C, and liquid bromine (chloroform solution, cumulative content 0.82 g, 5.15 mmol) was added dropwise in four portions. The reaction was monitored by thin-layer chromatography until compound 22 was completely reacted, for a total of 8 h. The mixture was washed three times with 100 mL of water, dried, and purified by column chromatography to give a yellow powder solid (590 mg, yield 91%). 1 H NMR(500MHz,Chloroform-d)δ6.95(d,2H),3.84(d,2H),1.99(m,1H),1.45–0.89(m,14H)

[0079]

[0080] Example 4: Preparation of polymer P1 containing benzodioxane units

[0081] Monomer M1 (300 mg, 0.406 mmol) and the common D-unit monomer 4,8-bis[5-(2-ethylhexyl)-4-fluoro-2-thienyl]benzo[1,2-b:4,5-b']dithiophene (BDT-FT-2Sn) (381.6 mg, 0.406 mmol) were dissolved in 10 mL of chlorobenzene. Tetra(triphenylphosphine)palladium (25.8 mg, 0.022 mmol) was added under nitrogen protection, and the reaction was carried out at 120 °C for 96 h. After the resulting dark blue solution was brought to room temperature, it was precipitated in 500 mL of methanol. The product was collected by filtration to give a reddish-brown solid polymer (320 mg, yield 65%, high-temperature GPC: Mw = 341 kDa).

[0082]

[0083] Example 5: Preparation of polymer P2 containing benzodioxane units

[0084] Monomer M2 (300 mg, 0.398 mmol) and the common D-unit monomer 4,8-bis[5-(2-ethylhexyl)-2-thienyl]benzo[1,2-b:4,5-b']dithiophene (BDT-Th-2Sn) (360.2 mg, 0.398 mmol) were dissolved in 10 mL of chlorobenzene. Tetra(triphenylphosphine)palladium (18.4 mg, 0.016 mmol) was added under nitrogen protection, and the reaction was carried out at 120 °C for 96 h. After the resulting dark blue solution was brought to room temperature, it was precipitated in 500 mL of methanol. The product was collected by filtration to give a reddish-brown solid polymer (300 mg, yield 63%, high-temperature GPC: Mw = 420 kDa).

[0085]

[0086] Example 6: Preparation of polymer P3 containing benzodioxane units

[0087] Monomer M3 (300 mg, 0.401 mmol) and common D-unit monomers (4,8-bis(5-(dodecylthio)thiophene)benzo[1,2-B:4,5-B']dithiophene)bis(trimethyltin); 4,5-B']dithiophene)bis(trimethyltin) (433.9 mg, 0.401 mmol) were dissolved in 10 mL of chlorobenzene. Tetra(triphenylphosphine)palladium (23.2 mg, 0.020 mmol) was added under nitrogen protection, and the reaction was carried out at 120 °C for 96 h. After the resulting dark blue solution was restored to room temperature, it was precipitated in 500 mL of methanol. The product was collected by filtration to give a reddish-brown solid polymer (290 mg, yield 53%, high-temperature GPC: Mw = 220 kDa).

[0088]

[0089] Example 7: Fabrication of Polymer Photovoltaic Devices Based on Benzodioxane-Containing Polymers Using the benzodioxane-containing polymer photovoltaic active layer material P1 from Example 4, the benzodioxane-containing polymer photovoltaic active layer material P2 from Example 5, and the benzodioxane-containing polymer photovoltaic active layer material P3 from Example 6 as donor materials, and PFA as acceptor material, polymer photovoltaic devices were fabricated. The device structure was: ITO / PEDOT:PSS / active layer / PFN-Br (methanol 0.5 mg / mL) -1 The structure of PFA is shown in Formula III:

[0090]

[0091] The specific steps for fabricating this organic photovoltaic device are as follows:

[0092] (1) Cleaning of conductive glass ITO substrate: The ITO glass substrate is placed in acetone, isopropanol, detergent, deionized water and isopropanol in sequence for ultrasonic cleaning to remove any residues (such as photoresist) that may remain on the surface of the ITO glass substrate and to improve the interface contact. After cleaning, it is placed in a vacuum oven to dry.

[0093] (2) Place the ITO in an oxygen plasma etching instrument and bombard it with oxygen plasma for twenty minutes to thoroughly remove any organic matter that may remain on the surface of the ITO glass substrate.

[0094] (3) Spin-coat a hole transport interface PEDOT:PSS with a thickness of about 30 nm on ITO, and then heat-anneal at 100 °C for 20 minutes.

[0095] (4) In a glove box under a nitrogen atmosphere, polymer active layer materials P1, P2 and P3 were mixed with PFA at a mass ratio of 1:1 and dissolved in methyltetrahydrofuran to prepare a solution with a concentration of 5 mg / mL. After spin-coating an active layer with a thickness of 150 nm onto the PEDOT:PSS layer, the active layer was heated and annealed at 100 °C for 15 minutes on a heating stage to remove residual solvent and improve the morphology of the active layer film.

[0096] (5) In a glove box under a nitrogen atmosphere, spin-coat a layer of electron transport material with a thickness of 20 nm onto the active layer material. The material used is 0.5 mg / mL poly[(9,9-di(3'-(N,N-dimethylamino)propyl)fluorenyl-2,7-diyl)-ALT-[(9,9-di-n-octylfluorenyl-2,7-diyl)bromo(PFN-Br);

[0097] (6) Finally, the prepared device is placed in the vapor deposition chamber and an Ag electrode with a thickness of 100 nm is vapor deposited in a vacuum environment.

[0098] (7) The photoelectric conversion efficiency, current-voltage characteristic curve and dark current-voltage characteristic curve of polymer solar cell device were tested under an AM 1.5G simulated sunlight lamp.

[0099] The photoelectric performance of the prepared organic solar cell devices was tested, and the test results are shown in Table 1.

[0100] Table 1 Device parameters of organic solar cells

[0101]

[0102] As shown in Table 1, the organic solar cell device using P1 as the active layer donor material and PFA as the active layer acceptor material exhibits excellent photoelectric performance, with a short-circuit current density of 21.32 mA / cm², an open-circuit voltage of 0.82 V, a fill factor of 77.91%, and a final device efficiency of 13.62%. Similarly, the organic solar cell device using P2 as the active layer donor material and PFA as the active layer acceptor material also demonstrates excellent photoelectric performance, with a short-circuit current density of 15.68 mA / cm², an open-circuit voltage of 0.88 V, a fill factor of 77.07%, and a final device efficiency of 10.01%. Finally, the organic solar cell device using P3 as the active layer donor material and PFA as the active layer acceptor material also exhibits excellent photoelectric performance, with a short-circuit current density of 22.07 mA / cm², an open-circuit voltage of 0.88 V, a fill factor of 77.65%, and a final device efficiency of 15.08%. Figure 2 The voltage-current density curves are for organic solar cells with P1, P2, and P3 as donors and PFA as acceptor. Figure 3 The open-circuit voltage aging degradation test curves are shown for organic solar cells with P1, P2, and P3 as donors and PFA as acceptor.

[0103] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A class of polymer photovoltaic materials containing benzodioxane units, characterized in that... The chemical structural formula satisfies the general formula shown in Formula I below: ; Formula I; In Formula I, D unit is the electron-donating unit of the photovoltaic active layer, Ar1 and π bridge are conjugated fused ring units, A1 and A2 are electron-withdrawing units, and the degree of polymerization n is 5-300; The D unit is at least one of the following chemical structures: ; In Equation I, the π-bridge element is a coupling structure of one or at least two of the following: ; In Equation I, the Ar1 element is one of the following structures: ; In Formula I, units A1 and A2 are independent of each other and belong to one of the following structures: ; In the above structure, R1, R2, R3, R4, and R5 are relatively independent of H, and are halogens, substituted or unsubstituted groups of one of the following: alkyl groups having 1-20 carbon atoms, aryl groups having 6-20 carbon atoms, heteroaryl groups having 4-20 carbon atoms, aralkyl groups having 7-20 carbon atoms, heteroarylalkyl groups having 4-20 carbon atoms, aryloxy groups having 6-20 carbon atoms, heteroaryloxy groups having 4-20 carbon atoms, arylalkoxy groups having 7-20 carbon atoms, and heteroarylalkoxy groups having 4-20 carbon atoms; wherein substitution refers to a group formed by replacing one or more hydrogen atoms with at least one of halogens, branched alkyl groups, oxygen atoms, alkenyl groups, alkynyl groups, and aryl groups.

2. The polymer photovoltaic material containing benzodioxane units according to claim 1, characterized in that... The chemical structural formula is one of the following: ; ; ; The degree of polymerization, n, ranges from 5 to 300.

3. A method for preparing a polymer photovoltaic material containing benzodioxane units according to any one of claims 1-2, characterized in that... Specifically, the following steps are included: Polymers are generated via Stille coupling reaction using dihalogen monomers containing benzodioxopyrazine units and diorganotin monomers containing D units, catalyzed by tetrakis(triphenylphosphine)palladium or palladium acetate / tritert-butylphosphine. The specific reaction route is shown below, where X is either bromine or iodine: 。 4. The method for preparing the polymer photovoltaic material containing benzodioxane units according to claim 3, characterized in that: The polymerization reaction temperature is 100-150 ℃.

5. The method for preparing the polymer photovoltaic material containing benzodioxane units according to claim 3, characterized in that: The preparation method described above uses a specific approach for preparing the dibromo monomer containing a benzodioxanone unit, as follows: Under inert gas protection and an alkaline environment, a dioxane-6 ring structure is formed between the aromatic fused ring and the pyrazine via the Williamson reaction. The corresponding dibromo monomer product is then obtained via NBS or liquid bromine. A π-bridge unit is then attached via a Stille or Suzuki coupling reaction. Finally, the final dibromo monomer containing the benzodioxanone unit is obtained via NBS or liquid bromine for polymer synthesis. The specific reaction route is shown below: 。 6. The method for preparing the polymer photovoltaic material containing benzodioxane units according to claim 5, characterized in that: The alkaline environment is provided by one of cesium carbonate, potassium carbonate, sodium methoxide, and sodium tert-butoxide.

7. The application of the polymer photovoltaic material containing benzodioxane units according to any one of claims 1-2 in polymer solar cells.

8. The application of the polymer photovoltaic material containing benzodioxane units according to claim 7 in polymer solar cells, characterized in that... Polymer photovoltaic materials containing benzodioxane units are polymer donor materials.

Citation Information

Patent Citations

  • Pyrazindithiophene derivatives and preparation method thereof

    CN103059041A

  • Method for Manufacturing Triarylpyrazine Derivative

    US20090183982A1